2020
DOI: 10.1108/jeim-04-2019-0118
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting eWOM credibility, information adoption and purchase intention on Generation Y: a case from Thailand

Abstract: PurposeWith the ever-expanding online shopping, electronic word-of-mouth (eWOM) has become a significant factor affecting the consumer decision-making behaviour. This is specially the case when considering Generation Y (Millennials), who are old enough to be independent buyers and young to be almost immersed in online living. This article aims to assess the impact of eWOM on purchase intention by developing a conceptual model of hypotheses encompassing a multitude of factors that may be associated with this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 77 publications
4
42
0
3
Order By: Relevance
“…First, they demonstrated the connection between moderators previously explored and purchase attribution (Shahab et al, 2020), which has not yet been seen. Second, The behavior of purchasing intentions supports previous literature, finding that trust allows consumers to buy from or recommend this to others (Ahmad et al, 2020). in particular, proven engagements generate greater attention and a better understanding of the message of a product (Celsi, R. L., & Olson, 1988); and consumers use more time devoted to finding information about a product (Bloch, Sherrell, & Ridgway, 1986); deeper information processing (Burnkrant, R. E., & Sawyer, 1983) and broader elaboration of the product.…”
Section: E-wom Trust and Purchase Intentionsupporting
confidence: 67%
See 2 more Smart Citations
“…First, they demonstrated the connection between moderators previously explored and purchase attribution (Shahab et al, 2020), which has not yet been seen. Second, The behavior of purchasing intentions supports previous literature, finding that trust allows consumers to buy from or recommend this to others (Ahmad et al, 2020). in particular, proven engagements generate greater attention and a better understanding of the message of a product (Celsi, R. L., & Olson, 1988); and consumers use more time devoted to finding information about a product (Bloch, Sherrell, & Ridgway, 1986); deeper information processing (Burnkrant, R. E., & Sawyer, 1983) and broader elaboration of the product.…”
Section: E-wom Trust and Purchase Intentionsupporting
confidence: 67%
“…Thus, at least one party is interested and actively seeking product-related information. However, unfortunately, this study does not consider unsolicited e-WOM and can be found on Instagram by individuals who may not even be interested in the brand in question (Ahmad et al, 2020). but are related to the brand's communication exchange that is 'connected' with members of the brand community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various researches have studied information sidedness in past literature and considered it as an important factor of online reviews (Chen et al, 2014;Daowd, Hasan, Eldabi, Rafi-Ul-Shan, Cao & Kasemsarn, 2020;Garg & Pandey, 2020;Hu et al, 2012;Purnawirawan et al, 2012;Qiu et al, 2012;Shih & Sung, 2020;Xue & Zhou, 2010;Wang, Li & Liu, 2020;Zhang, Craciun & Shin 2010). Thus, we hypothesize: H3: Information Sidedness positively influences Information Usefulness.…”
Section: 13) Information Sidednessmentioning
confidence: 93%
“…Consumers receiving messages are more identified with noncommercial/informal sources because they understand them as more authentic, more realistic, similar to themselves [42,43]. Therefore, consumers' behavior is influenced by the messages sent by someone similar to them [44,45].…”
Section: Perceived Source Expertisementioning
confidence: 99%